Meningococcal carriage in adolescents in the United Kingdom to inform timing of an adolescent vaccination strategy. - Jeppesen, C; Snape, M; Robinson, H; Gossger, N; John, T; Voysey, M; Ladhani, S; Okike, I; Oeser, C; Kent, A; Oliver, J; Taylor, P; et al. (Elsevier, 2015)
OBJECTIVES: Recent development of serogroup B meningococcal (MenB) vaccines highlights the importance of pharyngeal carriage data, particularly in adolescents and young adults, to inform implementation strategies. We describe current UK carriage prevalence in this high risk population and compare methods of carriage detection. METHODS: In this multisite study, pharyngeal swabs were collected on 3-4 occasions over 6-12 months, from 1040 school and university students, aged 10-25 years. Meningococcal carriage was detected by standard culture combined with seroagglutination or PCR of cultured isolates, or by direct PCR from swab. The factor H binding protein (fHBP) variants present in meningococcal isolates were determined. RESULTS: Meningococcal serogroups B and Y were most common, with carriage up to 6.5% and 5.5% respectively, increasing throughout adolescence. Identification by seroagglutination was often unreliable, and the sensitivity of direct PCR detection was 66% compared to culture combined with PCR. Of MenB isolates, 89.1% had subfamily A variants of fHBP. The acquisition rate of MenB carriage was estimated at 2.8 per 1000 person-months. CONCLUSIONS: If vaccination is to precede the adolescent rise in MenB carriage, these data suggest it should take place in early adolescence. Studies assessing vaccine impact should use molecular methods to detect carriage.